Case Report: Novel ASAP1::BRAF fusion in a young adult with low-grade temporal lobe glioma - Gerasimou, Petroula; Vrachnos, Dimitris; Kyprianou, Yiannos; Elpidoforou, Agathi; Miltiadous, Andri; Mitsidou, Andri; Nicolaou, Katerina; Shianiou, Gabriella; Zartila, Christina; Ioannou, Christina; Christofi, Andrea; Georgiou, Efi; et al. (Frontiers in Oncology, 2026)
Alterations involving the mitogen-activated protein kinase (MAPK) pathway are central drivers of pediatric and adult low-grade gliomas (LGGs), with BRAF fusions representing a dominant oncogenic mechanism in pilocytic astrocytoma. While KIAA1549::BRAF remains the most prevalent fusion, an expanding repertoire of alternative fusion partners continues to refine the molecular landscape of MAPK-driven gliomas and has important therapeutic implications. Here, we report a previously unrecognized ASAP1::BRAF fusion identified in a young adult with a World Health Organization grade 1 temporal lobe pilocytic astrocytoma, highlighting both its biological plausibility and potential relevance for targeted therapy. A 31-year-old female presented with new-onset seizures and underwent gross total resection of a well-circumscribed, partially cystic left temporal lobe tumor. Histopathological and immunohistochemical findings were consistent with pilocytic astrocytoma, demonstrating low proliferative activity and absence of high-grade features. Comprehensive molecular profiling using RNA-based next-generation sequencing revealed an in-frame ASAP1 exon 29::BRAF exon 9 fusion, preserving the intact C-terminal BRAF kinase domain while eliminating N-terminal regulatory regions. No additional pathogenic variants were detected. To substantiate the structural authenticity of the fusion, deep learning–based breakpoint validation using FusionAI was performed, yielding a high fusion probability score and supporting a bona fide genomic rearrangement rather than an RNA-sequencing artifact. Genomic feature annotation demonstrated enrichment of repetitive elements, regulatory regions, and chromatin accessibility features flanking the breakpoint, consistent with known mechanisms of fusion gene formation. Functionally, the ASAP1::BRAF fusion is predicted to emphasize constitutive MAPK pathway activation via dimer-dependent BRAF signaling, analogous to canonical BRAF fusions and mechanistically distinct from BRAF V600E mutations. Clinically, BRAF fusion–driven tumors are typically resistant to first-generation BRAF inhibitors but may be sensitive to MEK inhibitors or emerging type II RAF inhibitors that effectively target RAF dimers. Although no adjuvant therapy was required following complete resection, documentation of this fusion provides a rational framework for future molecularly guided treatment should disease recurrence occur. This case expands the spectrum of oncogenic BRAF fusion partners in LGG and underscores the importance of integrated RNA-based diagnostics and computational validation in precision neuro-oncology.